Peran Pelayanan Pastoral dalam Internalisasi Nilai Ekoteologi pada Kehidupan Jemaat: Tinjauan Kualitatif - Budiono, Gangsar; Sukmonoadji, Bambang; Ambariska, Yeni; Jonathans, Kornelius Rulli (Sekolah Tinggi Teologi Kadesi Bogor, 2026)
The environmental crisis has emerged as an urgent global challenge requiring a holistic response from various institutions, including the church. This qualitative study, employing a desk research approach, seeks to analyze the role of pastoral care in internalizing ecotheological values within congregational life. The findings reveal a significant gap between theological awareness and the daily environmental practices of congregants. The study identifies three principal forms of ecology-based pastoral care: liturgical and homiletic transformation, contextual education and catechesis, and community accompaniment and action. The internalization of ecotheological values unfolds through cognitive, affective, and conative stages and is shaped by supporting factors such as a strong theological foundation and visionary pastoral leadership, as well as inhibiting factors including theological anthropocentrism and routine-driven church practices. The study concludes that integrated and contextual pastoral care holds substantial potential to bridge the gap between faith and ecological practice, thereby enabling the church to contribute meaningfully to addressing the environmental crisis. Furthermore, the implications of this research highlight the need to reorient theological education curricula and to develop more practical and transformative models of pastoral care.